Pengaruh komitmеn kеsеlаmаtаn tеrhаdаp hubungan di antara psikososiаl pеrsеkitаrаn pеkеrjааn dan gеlаgаt selamat dаlаm kаlаngаn pеkеrjа sokongan Hospitаl Sultаn Abdul Hаlim, Kеdаh - Nordin, Kamis (2020)
Safe behavior, safety and psychosocial commitment to the work environment are among the important roles in developing a safe work culture in the workplace. This study aims to test the relationship between safe behavior, safety commitment on the psychosocial work environment. This quantitative study involved a total of 220 respondents where questionnaires were distributed to employees of the hospital support services company (HSS) at the Sultan Abdul Halim Hospital Sg. Petani Kedah. Statistical Package for Social Science (SPSS) version 26 was used to analyse the data of this study. Descriptive analysis shows that the level of safe behaviour practiced by HSS is at a moderate level while the level of security and psychosocial commitment of the work environment among employees of HSS companies is also moderate. Correlation and regression analysis, on the other hand, showed workplace pressures, job organization and work content, interpersonal relationships and leadership, individual-work relationship factors, workplace values, health and wellbeing relationships. The role of safety commitment as a mediator in the relationship between safe behavior and psychosocial work environment can be concluded to have a significant impact. The role of employers needs to be more robust in enforcing rules and regulations to employees in HSS companies. The relationship between employer and employee also requires tolerance and it will be gradually to achieve the company occupotional safety goal.